A multicenter single‐arm trial of neoadjuvant pyrotinib and trastuzumab plus chemotherapy for HER2‐positive breast cancer - Qiyun Shi; Xiaowei Qi; Peng Tang; Linjun Fan; Li Chen; Shushu Wang; Yan Liang; Ying Hu; Minghao Wang; Lin Ren; Guozhi Zhang; Xuanni Tan; et al. (MedComm, 2023)
Abstract The objective of this multicenter, single‐arm trial (ChiCTR1900022293) was to explore the efficacy and safety of neoadjuvant therapy with epirubicin, cyclophosphamide, and pyrotinib followed by docetaxel, trastuzumab, and pyrotinib (ECPy‐THPy) in the treatment of patients with stage II–III HER2‐positive breast cancer. The present study enrolled patients with stage II–III HER2‐positive breast cancer. Epirubicin and cyclophosphamide were administrated for four 21‐day cycles, followed by four cycles of docetaxel and trastuzumab. Pyrotinib was taken orally once per day throughout the treatment period. The primary endpoint was total pathological complete response (tpCR, ypT0/is ypN0) rate in the modified intention‐to‐treat (mITT) population. In total, 175 patients were included. The tpCR rate was 68.6% (95% CI, 60.7–75.8%), while the objective response rate was 89.1%. In the post‐hoc subgroup analysis, no association between clinical characteristics and the tpCR rate was observed. The most common grade ≥3 adverse events were diarrhea (54.3%), followed by white blood cell count decreased (5.1%), and neutrophil count decreased (4.6%). In conclusion, the neoadjuvant regimen with ECPy‐THPy showed promising pathological response and clinical benefits with an acceptable safety profile in patients with stage II–III HER2‐positive breast cancer.